Analysis of the Skills Gap between Engineering Graduates and the Needs of the Manufacturing Industry in Melaka - Muhammad Syazwan; Nurul Izzah (Al Kautsar: Knowledge Advancements in Teaching Strategies and Research, 2026)
The manufacturing sector in Melaka is undergoing a rapid transformation toward Industry 4.0, yet its success is hindered by a significant skills gap between engineering graduates and industrial requirements. This study aims to analyze the dimensions of the skills gap, the impact of Skill-Biased Technological Change (SBTC) as a driver of job polarization, and structural issues such as the "Poor Engineer" phenomenon in Melaka. Using a systematic literature review and secondary data analysis from the Department of Statistics Malaysia (DOSM) and industrial reports, the study finds that the most critical gaps exist in digital communication, complex problem-solving, and data/AI literacy. The analysis reveals that the "Poor Engineer" phenomenon, where 35% of graduates receive salaries below RM 2,000, is driven by a misalignment between graduate competencies and the high standards of Industry 4.0, leading to a skill-related underemployment rate of 32.2%. Although Universiti Teknikal Malaysia Melaka (UTeM) records a high employability rate (96.4%), the quality of job placement is still dominated by technician-level positions, indicating that employability does not necessarily reflect a successful skill-match. This research recommends aligning curricula through Teaching Factory models, enhancing digital literacy, and urging a government review of minimum wage structures for technical graduates to retain talent and ensure national technological sovereignty.